The Indian Scientific Community and the Stock Market : Impact of the COVID-19 Lockdown - Upadhyaya, Samiran (Indian Journal of Research in Capital Markets, 2024)
Purpose : The present study presented a detailed analysis of the growing interest of the scientific community in Indian share market trading. The work also highlighted the key role played by the COVID-19 lockdown in the growth of the share market trading and investments. Methodology : A total of 250 participants were involved in carrying out the survey required for this article with due consent. All procedures performed in studies involving human participants were in accordance with the ethical standards of our institute and with the 1964 Helsinki Declaration and its later amendments or comparable ethical standards. Findings : From the survey, it was found that the total active traders from the science background had increased significantly from 11.5% to 34% since the COVID-19 lockdown, which could be viewed as a positive change. Most of the traders from the scientific community still preferred mutual funds or long-term investments over short-term trading strategies. Practical Implications : It was recommended time and again that most Indians should invest in the share market (through proper knowledge) and make the most of it. The COVID-19 lockdown proved to be a blessing in disguise for the Indian scientific community, who have gathered knowledge and started the investment in the share market. This study showed the behavior and pattern of investments of the scientific forum in our country. Our study was not free from limitations and allowed scope for future researchers to delve more into the area. Originality : Unlike prior research on the various aspects of the share market, the current work presented the behavioral pattern of the scientific community toward share market trading and investments. Moreover, this study highlighted the impact of the COVID-19 lockdown on the investment pattern of the above-stated group/community.